Henry Savile and the Elizabethan Court - Gajda, A (Brill, 2021)
This essay examines Henry Savile’s relationship with the Elizabethan and Jacobean court and the political culture of the period in which he lived. Particular attention is paid to the controversies surrounding Savile’s alleged connection to Robert Devereux, 2nd earl of Essex and the court politics of the 1590s, and variant interpretations scholars have made of the political significance of his historical scholarship. Savile’s Elizabethan literary remains demonstrate his persistent interest in the association between militarism and the arts of civil government, and the frequently problematic relationship of virtuous soldiers and statesmen to princely rulers. These concerns were shared by leading Elizabethan soldiers and statesmen, from the earl of Leicester, William Cecil, Lord Burghley, to the earl of Essex, and may have influenced the latter’s growing alienation from queen and court in the late 1590s. A broader comparison of Savile’s career with those of contemporary Merton scholars, however, confirms that he rejected the public careers pursued by other friends and colleagues. Savile’s political connections seem to have served his scholarly ambitions rather than the other way around, and after the rebellion of the earl of Essex he seems to have retreated from life at court.